Revitalization of the Values of Ngelamping Ceremony in Cultural Tourism Management in Bali - I Made Sujanayasa; I Ketut Suarja; Ni Ketut Riska Dewi Prawita; Ni Nyoman Tri Thika Dewanthari; I Putu Ari Utama Irawan (Journal of Practice Learning and Educational Development, 2026)
This study examines in the belief that the Ngelamping ceremony, as part of Dewa Yadnya, plays a fundamental role in maintaining the balance of human relations with God, nature, and community. The tradition is not merely a religious expression but also an act of gratitude among Balinese agrarian communities for abundant harvests. The research employed a qualitative method through literature review and participatory observation in Bukian Traditional Village. The findings reveal that Ngelamping has a strong theological foundations based on yadnya, embodies fertility symbols through ritual offerings (upakara), and functions as a medium to strengthen social solidarity and customary institutions. Furthermore, its implementation based on the Balinese wariga calendar (the traditional Balinese calendrical system) underscores the importance of cosmic harmony in Balinese life. These findings highlight the relevance of Ngelamping as a cultural heritage that is both sacred and strategic for identity preservation and sustainable development.